Experience report of an academic League of Management and Innovation in Health (LAGIS) (Research, Society and Development, 2023)
The purpose of this article is to report the experiences of the Academic League on Management and Innovation in Health (ALMIH) in the year 2021/2022. This is a descriptive, qualitative study of the experience report type, about the experience of LAGIS members, in the municipality of Belém-Pará, addressing the functioning and organization of extracurricular activities developed by the League and the learning methods developed from actions related to Management such as teaching, research, extension and knowledge directed to courses in the health area and academic training. LAGIS is based on the 3 teaching, research and extension pillars in which the students who make up the league take an active role in the teaching-learning process, deepening knowledge about Management and Innovation in health for all professionals in the area, strengthening the Management in the multiprofessional context of health. It should be noted that LAGIS is not intended to interfere in the academic training process, but rather to add learning and more knowledge to the academic being more solid. From the initial concepts of management to practice that involves knowledge how to innovate within the health system. In order to improve with excellence the role of the Health Manager for a better service to the population.